Patossistema maracujazeiro-Fusarium spp. : melhoramento genético e estudo de resposta de defesa - Chimello, Antonio Marcos (2021)
Brazil is the world's largest producer of passion fruit, mainly with the species Passiflora edulis Sims (90%), popularly known as passion fruit, yellow or purple. Although there is a growing interest of producers in the cultivation of passion fruit, due to its high price and utility, it has been observed that in recent years there has been a reduction in the planted area and in fruit production. Different factors contribute to this, such as low productivity, use of inadequate cultivation techniques and low use of improved cultivars. In addition, diseases caused by fungi of the Fusarium genus stand out, such as fusariosis caused by the fungus Fusarium oxysporum f.sp. passiflorae and collar rot, caused by the Fusarium solani species complex. In areas with a history of these diseases and without the possibility of rotating planting in new areas, there are no efficient control measures for these diseases. Therefore, an alternative to solve the problems with these diseases is the development of cultivars resistant to phytopathogens, through the transfer of resistance genes present in wild Passiflora species. This work aims to obtain and evaluate genotypes of the first generation of backcrossing passion fruit plants resistant to soil fungi, evaluate alternative methods of control of soil diseases, such as: use of resistant Interspecific Hybrid as rootstock and actinobacteria as biological control and, finally, to evaluate the biochemical defenses of plants by enzymatic activity. The experiments were carried out in the experimental area and in the Plant Genetic Improvement Laboratory of the State University of Mato Grosso (UNEMAT), campus of Cáceres-MT. The backcrosses were carried out with hybrids resistant to collar rot, from the cross between Passiflora edulis Sims and Passiflora nitida (resistance gene donor). As a recurrent parent, genotypes of P. edulis cultivar BRS Sol do Cerrado were used. The hybrid UNEMAT 115 resulting from the cross between P. edulis and Passiflora quadrangularis, with high resistance to stem rot, was used as a full slit fork rootstock, with the crowns from the species P. edulis cultivar BRS Sol do Cerrado. For the evaluation of grafting, morphoagronomic descriptors suggested by MAPA were used. To evaluate the antagonist power between actinobacteria and isolates from the F. solani species complex, the actinobacterium Streptomyces griseocarneus, isolate R132, previously isolated from Paullinia cupana roots, was used. First, the antibiosis assay in paired culture (in vitro) was performed, then the biological control capacity of S. griseocarneus R132 with F. solani isolates was tested. Furthermore, in the present study, the biochemical defense response capacity of passion fruit plants resistant and susceptible to the fungi F. solani and F. oxysporum f.sp. passiflorae was investigated, quantifying the activity of the enzymes peroxidase and β-1,3- glucanase. The results obtained indicate that the generation advance by the backcross method, of resistant hybrids and commercial cultivars of P. edulis as recurrent parent, provided the formation of genotypes of the first generation of backcrosses resistant to collar rot. Demonstrating that the backcrossing method was efficient for transferring genes of interest in the passion fruit breeding program. Alternatively, the use of the interspecific hybrid UNEMAT 115 as rootstock and the bacterium S. griseocarneus R132 as biological control were effective in significantly reducing the damage caused by the cervical rot disease. HI UNEMAT 115 as rootstock did not show significant difference between grafted and blunt plants, for characteristics related to production, physical and chemical quality of the fruits or for the morphology of the crowns. The antifungal potential of S. griseocarneus R132 was observed against all F. solani isolates, when evaluated in vitro. In the evaluation of biological control actinobacterium significantly reduced the damage caused by the disease compared to untreated plants, suggesting potential as a biocontrol agent. Therefore, these techniques can be used as a preventive form of control in areas with a history of occurrence of cervical rot disease.